The Influence of Trust and Service Quality on Online Shop Interested in Buying - Muntaha, Ulul (LPPM Universitas Bina Bangsa, 2021)
In this 4.0 generation, buying and selling online is very popular. Convenience, various choices and various promotions offered are the main factors behind this 4.0 generation purchasing online. This can also be seen from the change in buying styles from traditional markets to online stores, which are increasing. Although there are many advantages and disadvantages of buying and selling online, some consumers are not satisfied with their online purchases. This is due to the seller's lack of service and consumers' doubts about buying because the goods sent by the seller are often not following the order, thereby reducing the value of consumer confidence in buying and selling online. Based on this phenomenon, this study aims to determine the effect of trust and service quality on online shop buying interest with a case study of Islamic Business Economics Faculty students. The number of stamps used is 150 people